STUDI PENINGKATAN INTENSITAS LUAS DAN POLA TANAM PADA DAERAH IRIGASI KRUENG JREUE - Faisal Faisal; Alfiansyah Yulianu; Ella Mailianda (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2018)
Krueng Jreue irrigation area is one of the oldest irrigation in Aceh Besar district, located in the District of Indrapuri, was inaugurated in 1972 by President Soeharto. Rice area irrigated by this irrigation is 4277.6 ha. Jreue Krueng irrigated areas have rice-rice cropping intensity of plants ranging from 158% to 156%. The intensity of these plants are still below the expected crop intensity, is equal to 200%. To increase the intensity of these plants, it is necessary to study the increased intensity of Krueng Jreue tanamana irrigation area by selecting the appropriate alternative cropping patterns according to the water balance. This study aims to determine the amount of discharge mainstay available on the weir, know the size of the crop water requirement for each alternative, determine optimal crop area that can be irrigated by water that is available, and conduct studies on water balance based cropping planned. Expected to describe the water balance of alternative cropping patterns were obtained. The method used in this research including data collection and data analysis to determine the mainstay discharge, water irrigation, cropping pattern and cropping intensity. The study results obtained by the intensity of the plants can reach 200% by the water supply system using the technical rotation irrigation area is divided into two groups. The first type, cropping season from October period to 2. The second class of the cropping season from November to 2.